UPAYA GURU MENGEMBALIKAN KONSENTRASI BELAJAR PADA SISWA KELAS IIB DI SDS IT Al-FURQON TEBAS TAHUN PELAJARAN 2023-2024 - Darul Hafizi; Ahmad Rathomi; Asyruni Multahada (CV. ADIBA AISHA AMIRA, 2024)
Student learning concentration is very important in the success of the learning process carried out by the teacher. This research aims to determine teachers' efforts to restore students' learning concentration. This research was conducted using qualitative research with a descriptive approach. Data collection was carried out through observation, interviews and documentation. The location of the research was SDS IT Al-Furqon Tebas, Sambas Regency, West Kalimantan Province. Interviews were conducted with grade 2 teachers, school principals, and students. Data analysis techniques use Milles and Huberman, namely, Data Reduction, Data Display, and Conclusion Drawing. The conclusions of this research are three problems in student learning concentration, namely cognitive behavior, affective behavior, and psychomotor.